Resonant Auger decay of core-excited CO molecules in intense x-ray laser pulses: the O(1s → π*) excitation - Demekhin, Philipp V.; Cederbaum, Lorenz S. (Journal of physics. B, Atomic, molecular and optical physics, 2013)
The dynamics of the resonant Auger (RA) decay of the core-excited CO*(1s−1π*) molecule in intense x-ray laser pulses is studied theoretically. The present approach includes the impact of the analogue of conical intersections of the complex potential energy surfaces of the ground and ‘dressed’ resonant states induced by intense x-ray pulses. It also takes into account the decay of the resonance and the direct photoionization of the ground state, both populating the same final ionic states coherently, as well as the direct photoionization of the resonance state itself. The individual impacts of these physical processes on the total ion yield, the CO+(A 2Π) electron spectrum and the ro-vibrational distributions of the neutral molecules remaining in the ground electronic state after the laser pulse has expired are analysed and compared to those reported previously for the C*O resonance. It is also demonstrated that the RA effect of molecules by strong laser pulses of resonant carrier frequency is an efficient process to produce two-site double-core-hole-one-particle states of CO*.
Gesehen am 11.12.2020